JURIDICAL REVIEW OF THE CRIME OF SALAK FRUIT THEFT BASED ON ARTICLE 362 OF THE CRIMINAL CODE (A CASE STUDY AT THE DELI SERDANG CITY POLICE) - Niko Kristopal; Muhammad Hizbullah (CV. Barokah Publsiher, 2026)
This study aims to analyze the form and elements of the criminal offense of stealing salak (snake fruit) based on Article 362 of the Indonesian Criminal Code (KUHP), as well as to examine law enforcement against the perpetrators of such theft from a juridical perspective. The results of the study show that the criminal offense of stealing salak in the jurisdiction of Polresta Deli Serdang fulfills all the elements stipulated in Article 362 of the KUHP. The element of “whoever” is fulfilled because the perpetrator is a legal subject capable of bearing criminal responsibility. The element of “taking an object” is proven by the act of the perpetrator who took salak from a plantation without the owner’s permission. Salak, as an agricultural product, has economic value and falls within the category of property under criminal law. Therefore, the theft of salak can juridically be classified as a criminal offense of theft. The element of “wholly or partly belonging to another person” is established through the statements of the victim and witnesses around the scene of the incident, as ownership of the plantation and its produce forms the basis for legal protection of the victim. Furthermore, the element of “with the intent to unlawfully possess” can be inferred from the perpetrator’s attitude and actions in carrying or controlling the salak without legal right. Justifications such as merely taking the fruit for consumption do not negate the unlawful nature of the act. Accordingly, both normatively and empirically, the elements of Article 362 of the KUHP are cumulatively fulfilled